1988
DOI: 10.1177/0146167288142005
|View full text |Cite
|
Sign up to set email alerts
|

The Illusion of Unique Invulnerability and the Use of Effective Contraception

Abstract: It was proposed that one reason people often fail to use effective contraception methods is that they engage in a systematic distortion of their likelihood of being involved in an unwanted pregnancy relative to others. A survey of undergraduate females found that sexually active women tended to see themselves as less likely than other students, other women their age, and women of childbearing age to become pregnant. The tendency to utilize this illusion of unique invulnerability was related to the use of effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
69
1
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(76 citation statements)
references
References 8 publications
5
69
1
1
Order By: Relevance
“…A wealth of research has found that people view the future through rose-tinted glasses, believing that they are more likely than others to undertake positive behaviors or to experience positive events and are less likely to experience negative events or to undertake negative behaviors (Armor and Taylor 2002;Burger and Burns 1988;McKenna 1993;Perlof and Fetzer 1986;Taylor and Brown 1988;Weinstein 1980). Such unrealistic optimism effects (sometimes called comparative optimism or illusory optimism effects) occur whether people are making explicitly comparative judgments (e.g., "Compared to an average student, how likely are you to catch an STD in the next year?")…”
Section: Unrealistic Optimismmentioning
confidence: 99%
See 1 more Smart Citation
“…A wealth of research has found that people view the future through rose-tinted glasses, believing that they are more likely than others to undertake positive behaviors or to experience positive events and are less likely to experience negative events or to undertake negative behaviors (Armor and Taylor 2002;Burger and Burns 1988;McKenna 1993;Perlof and Fetzer 1986;Taylor and Brown 1988;Weinstein 1980). Such unrealistic optimism effects (sometimes called comparative optimism or illusory optimism effects) occur whether people are making explicitly comparative judgments (e.g., "Compared to an average student, how likely are you to catch an STD in the next year?")…”
Section: Unrealistic Optimismmentioning
confidence: 99%
“…They exist in situations where individuals have substantial influence over outcomes (behavioral predictions) as well as in settings where fate plays a more significant role (likelihood estimates). Examples of the behavioral predictions include optimistic estimates that one will get a good first job (Weinstein 1980), avoid an unwanted pregnancy (Burger and Burns 1988), and avoid addiction to drugs (Weinstein 1987). Examples of optimistic likelihood estimates include unrealistically low estimates for the likelihood one will contract lung cancer (Perlof & Fetzer 1986), be in a car accident (McKenna 1993) or be the victim of a crime (Perlof & Fetzer 1986).…”
Section: Unrealistic Optimismmentioning
confidence: 99%
“…In some cases, they lead to a complacency in which people ignore legitimate risks (Lehman & Taylor, 1988;Weinstein, 1982) and fail to take necessary actions or precautions (Perloff, 1983). For example, college women who harbor illusions of "unique invulnerability" about becoming pregnant are less likely than others to use effective contraception (Burger & Burns, 1988). Similarly, people who believe they will not become sick are less likely than others to immunize themselves against the flu (Larwood, 1978).…”
mentioning
confidence: 99%
“…Age-specific under· standing of children's comparative risk judgments is important not only for the formulation of intervention programs but also because, at least in adults, risk perceptions have been linked to risky actions. In a study of contraceptive use, for example, Burger and Burns (1988) found that higher levels of optimistic bias regarding the probability of experiencing unwanted pregnancy were associated with lower rates of effective contraception. Risk perceptions may also be linked to behavioral intentions, as illustrated by a recent report that high school students' perceived vulnerability to AIDS was associated with their intentions to change risk -promoting behaviors (Gladis et al, 1992).…”
mentioning
confidence: 99%